Explainability Analysis of the Evaluation Model of the Level of Digital Transformation in MSMEs based on Fuzzy Cognitive Maps (2024)
the concept of digital transformation involves exploiting digital technologies to generate new ways of doing things in organizations, including the creation of new processes, models, and services that produce value based on the digitization of data and processes. The application of digital technologies enables organizations to develop capabilities for innovation, automation, etc., utilizing both established and emerging technologies, including the widespread use of artificial intelligence. This article proposes the implementation of Fuzzy Cognitive Maps (FCMs) based on experts and data for the evaluation of the level of digital transformation in MSMEs (Micro, Small and Medium Enterprises). Additionally, this work carries out an explainability analysis of the evaluation models based on FCMs. The main digital transformation variables used to define our FCMs were classified into five groups, based on the COBIT standard: i) Organization and Culture variables related to strategies, way of working, and ecosystems, ii) Customer variables related to services and digital channels and products, iii) Operations and Internal Processes variables related to supply chain, suppliers, and business model, iv) Information Technologies variables related to innovation, digitization, data and analytic. Finally, the fifth type of variable is the target, which indicates the level of digital transformation of the organization. Our model managed to specify with 99.4% the level of digital transformation of the organization. Furthermore, the explanatory capacity of the FCMs developed in this work was explored using different explainability methods, some general and others specific to the FCMs. In general, the results obtained in the work are very encouraging since the quality metrics obtained with the evaluation models are very good, almost always higher than 90%; and the explanations obtained with the explainability methods allow for an in-depth analysis of the behavior of the variables in the results obtained, something very important to understand how to improve the levels of digital transformation in organizations.